Nutrition Physiology and Metabolism in Spaceflight and Analog Studies - Heer, Martina; Titze, Jens; Smith, Scott M.; Baecker, Natalie (SpringerBriefs in Space Life Sciences, 2015)
This book provides an overview of microgravity-induced changes in human metabolism, muscle, bone and the cardio-vascular system, and discusses in detail the nutrient uptake required during spaceflight to counteract these adaptive mechanisms and ensure an improved physical constitution upon returning to Earth. It addresses the needs of professors, researchers and students working in the field of human physiology and nutrition.